Sebuah PENGEMBANGAN MEDIA PEMBELAJARAN ALAT KOMUNIKASI ANTAR-LAB UNDIKSHA BERBASIS IOT LORA PADA MATA KULIAH MIKROKONTROLER - Nugraha Jati, Ketut Vira; I Gede Made Surya Bumi Pracasitaram; Agus Adiarta (Universitas Pendidikan Ganesha, 2025)
This research aims to create learning media that is implemented in IoT and Lora-based communication tools between fishermen which are used to assist the learning process in the Microcontroller course in the Undiksha Electrical Engineering Education Study Program. This research is included in the type of R&D (Reasearch and Development). This research uses percentage statistical analysis techniques to process data from content experts, media experts, and field trials. This research uses a questionnaire as an instrument for collecting data from content experts, media experts and students. The research results obtained: The content expert test results obtained a percentage of 96% with very decent qualifications, the media expert test results obtained a percentage of 95% with very decent qualifications. The test results for the small group of respondents had the lowest score, namely respondent 1 (R1) with a score of 65, which was classified as very good, and the test results for the large group showed the lowest score for respondents, namely respondent 2 (R3) with a score of 60, which was included in the good classification. Based on the research results, IoT and Lora-based Communication Tool Learning Media between Fishermen is suitable for use in the learning process in the Microcontroller Course in the Undiksha Electrical Engineering Education Study Program.